2017
DOI: 10.1002/jsfa.8731
|View full text |Cite
|
Sign up to set email alerts
|

Development of functional extruded snacks by utilizing paste shrimp (Acetes spp.): process optimization and quality evaluation

Abstract: The study suggests that use of Acetes species for the development of extruded snacks will serve as a means of utilization of Acetes as well as being a rich source of proteins for human consumption, which would otherwise remain unexploited as a by-catch. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Crunchiness (N 0 ) presented significant ( p < 0.05) positive correlations with WSI; meanwhile, it was not positively correlated with a w . According to Lotfi Shirazi et al [ 48 ], the crunchiness of snacks is related to the thickness of the walls and with expansion, available water inside the product is necessary for its starch binding and thus to facilitate its gelatinization and expansion [ 49 ]. The significant ( p < 0.05) positive correlation between SEI and x w and a w can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…Crunchiness (N 0 ) presented significant ( p < 0.05) positive correlations with WSI; meanwhile, it was not positively correlated with a w . According to Lotfi Shirazi et al [ 48 ], the crunchiness of snacks is related to the thickness of the walls and with expansion, available water inside the product is necessary for its starch binding and thus to facilitate its gelatinization and expansion [ 49 ]. The significant ( p < 0.05) positive correlation between SEI and x w and a w can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…), which have a dominant effect on product quality. Due to such a huge number of independent (design and response) variables in extrusion, the use of response surface methodology (RSM) seems to be a logical approach for optimization of the process (Kumar et al, 2018). RSM solves multivariate equations and optimizes the process thus helping to find out the specific values of important variables that could produce optimum response.…”
Section: Introductionmentioning
confidence: 99%
“…The popularization of healthy lifestyles has led to an increase in the importance of nutritional value, as evidenced by the growing demand of food consumers for a higher content of protein and of dietary fiber [1]. BRDEM-2019 The researchers [2,3,5,8,11,13] note in the snacks on the market that they are high in fat and salt, high in calories, they are characterized by biological poverty and an unbalanced composition. Regular consumption of such products contributes to various deficiencies leading to the development of nutritional diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In studies [10--13], which confirmed the prospects and relevance of this area, developed snacks, which included offals of processing hydrobionts and ones from brewing industries. In [10], technology for fish crackers from minced tilapia, corn flour and starch was obtained, in [11] --functional extruded snacks using shrimp powder, in [12] --extruded fish and corn snacks, in [13] --malt grains were added to the extruded snacks.…”
Section: Introductionmentioning
confidence: 99%